2018
DOI: 10.35188/unu-wider/2018/572-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of commercialization of rice on household welfare in rural Vietnam

Abstract: This study has been prepared within the UNU-WIDER project on 'Structural transformation and inclusive growth in Vietnam'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Overall, rice marketing channels in Vietnam have developed remarkably since the economic renovation introduced in the late 1980s . There was a significant increase in the number of rice farmers participating in national rice markets (Cazzuffi and McKay, Cazzuffi and McKay ; Minot and Goletti ). The proportion of households selling rice countrywide increased from 42.8 percent in 1992–1993 to 54 percent in 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, rice marketing channels in Vietnam have developed remarkably since the economic renovation introduced in the late 1980s . There was a significant increase in the number of rice farmers participating in national rice markets (Cazzuffi and McKay, Cazzuffi and McKay ; Minot and Goletti ). The proportion of households selling rice countrywide increased from 42.8 percent in 1992–1993 to 54 percent in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…farm size and location) (Zivenge and Karavina ) and the farmers' sociodemographic characteristics, such as their educational level (Escobal and Cavero ) and age (Fischer and Qaim ), which have also been identified as determinants of farmers' marketing channel choice in previous studies of other cases and countries. Farm size is of particular interest in the context of Vietnamese SR production because indications exist that larger farmers tend to sell most of their products at the farm gate to local collectors and wholesalers in the TMC for simplicity reasons (Cazzuffi and McKay ). In contrast, smaller farmers producing a smaller amount of rice prefer to sell their products to farmer associations (MFA) and directly to end consumers (DMC).…”
Section: Introductionmentioning
confidence: 99%
“…Available data indicates that the contribution has declined from about 80 per cent in 2007 to about 68 per cent in 2017 (NBE, 2017). With a gradual increase in agricultural commercialisation, however, the engagement of smallholder farmers in the agricultural input and output markets, including labour markets, has increased considerably (Jaleta, Gebremedhin and Hoekstra, 2009;Cazzuffi, McKay and Perge, 2018). The growth of some agricultural commodities in Ethiopia -like sesame and coffee, among other high value export crops, and commercial crops such as rice, teff and common beans -has been highly dependent on the use of hired labour, especially for selected agronomic practices like weeding, harvesting and threshing.…”
Section: Acronyms Executive Summarymentioning
confidence: 99%
“…These rice-specialist districts have somewhat lower incomes and higher incidence of child malnutrition and poverty (Nguyen 2013). Cazzuffi et al (2018), using panel data from 2008 to 2016 for the whole of Vietnam, found that households selling a higher proportion of the rice they produced did not have significantly higher income or food consumption than those selling less rice, though they accumulated more assets. At the same time, households earning a higher proportion of total income from rice had lower income and no significant difference in asset accumulation.…”
Section: Diversification Of Rice-based Farming Systemsmentioning
confidence: 99%